Effects of stretching on upper-body muscular performance - Torres, E. M.; Kraemer, W. J.; Vingren, J. L.; Volek, J. S.; Hatfield, D. L.; Spiering, B. A.; Ho, J. Y.; Fragala, M. S.; Thomas, G. A.; Anderson, J. M.; Hakkinen, K.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this investigation was to examine the influence of upper-body static stretching and dynamic stretching on upper-body muscular performance. Eleven healthy men, who were National Collegiate Athletic Association Division I track and field athletes (age, 19.6 +/- 1.7 years; body mass, 93.7 +/- 13.8 kg; height, 183.6 +/- 4.6 cm; bench press 1 repetition maximum [1RM], 106.2 +/- 23.0 kg), participated in this study. Over 4 sessions, subjects participated in 4 different stretching protocols (i.e., no stretching, static stretching, dynamic stretching, and combined static and dynamic stretching) in a balanced randomized order followed by 4 tests: 30% of 1 RM bench throw, isometric bench press, overhead medicine ball throw, and lateral medicine ball throw. Depending on the exercise, test peak power (Pmax), peak force (Fmax), peak acceleration (Amax), peak velocity (Vmax), and peak displacement (Dmax) were measured. There were no differences among stretch trials for Pmax, Fmax, Amax, Vmax, or Dmax for the bench throw or for Fmax for the isometric bench press. For the overhead medicine ball throw, there were no differences among stretch trials for Vmax or Dmax. For the lateral medicine ball throw, there was no difference in Vmax among stretch trials; however, Dmax was significantly larger (p <= 0.05) for the static and dynamic condition compared to the static-only condition. In general, there was no short-term effect of stretching on upper-body muscular performance in young adult male athletes, regardless of stretch mode, potentially due to the amount of rest used after stretching before the performances. Since throwing performance was largely unaffected by static or dynamic upper-body stretching, athletes competing in the field events could perform upper-body stretching, if enough time were allowed before the performance. However, prior studies on lower-body musculature have demonstrated dramatic negative effects on speed and power. Therefore, it is recommended that a dynamic warm-up be used for the entire warm-up.